2022
DOI: 10.1038/s41434-022-00375-w
|View full text |Cite
|
Sign up to set email alerts
|

In vivo genome editing using novel AAV-PHP variants rescues motor function deficits and extends survival in a SOD1-ALS mouse model

Abstract: CRISPR-based gene editing technology represents a promising approach to deliver therapies for inherited disorders, including amyotrophic lateral sclerosis (ALS). Toxic gain-of-function superoxide dismutase 1 (SOD1) mutations are responsible for ~20% of familial ALS cases. Thus, current clinical strategies to treat SOD1-ALS are designed to lower SOD1 levels. Here, we utilized AAV-PHP.B variants to deliver CRISPR-Cas9 guide RNAs designed to disrupt the human SOD1 (huSOD1) transgene in SOD1 G93A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 68 publications
(116 reference statements)
0
0
0
Order By: Relevance
“…A follow-up Phase 1/2 study demonstrated that the administration of ASO-SOD1 resulted in a reduction in SOD1 protein levels in CSF [399] and a Phase 3 trial is currently underway (Tofersen). Additionally, RNA interference (RNAi) and CRISPR technology have been employed to downregulate mutant SOD1; a one-time intrathecal or intravenous injection of AAV-SOD1-sgRNA results in reduction in SOD1 levels, enhanced motor function, and significantly extended the lifespan of mice having mutant SOD1 [400]. Recently, a proofof-concept investigation demonstrated the feasibility of intrathecally delivering AAVs expressing microRNAs against SOD1 in two patients with SOD1-related ALS.…”
Section: Gene Therapy For Als Targeting Sod1mentioning
confidence: 99%
“…A follow-up Phase 1/2 study demonstrated that the administration of ASO-SOD1 resulted in a reduction in SOD1 protein levels in CSF [399] and a Phase 3 trial is currently underway (Tofersen). Additionally, RNA interference (RNAi) and CRISPR technology have been employed to downregulate mutant SOD1; a one-time intrathecal or intravenous injection of AAV-SOD1-sgRNA results in reduction in SOD1 levels, enhanced motor function, and significantly extended the lifespan of mice having mutant SOD1 [400]. Recently, a proofof-concept investigation demonstrated the feasibility of intrathecally delivering AAVs expressing microRNAs against SOD1 in two patients with SOD1-related ALS.…”
Section: Gene Therapy For Als Targeting Sod1mentioning
confidence: 99%